Kualitas Produk, Persepsi Harga Terhadap Kepuasan dan Dampaknya pada Niat Beli Ulang - Thifal Oksan Abiyyu; Endang Tjahjaningsih (IPM2KPE, 2023)
This research aims to determine the influence of product quality (X1), price perception (X2) on satisfaction (Y1) and the impact on repurchase intention (Y2) of ERIGO products in the city of Semarang. The research method used is a quantitative method. The data source used was a questionnaire via Google Form for 100 respondents with purposive sampling methodology. Hypothesis testing uses multiple linear regression tests using statistical-based data processing, namely SPSS 25. The research results show that product quality has a positive and significant effect on satisfaction, price perception has no effect on satisfaction and satisfaction has a positive and significant effect on repurchase intentions. The conclusion is that the better the quality of the product provided, the more satisfaction will increase. The same is true with satisfaction, the higher the level of satisfaction obtained, the higher the intention to repurchase. Keywords: Satisfaction, Product Quality, Repurchase Intention, Price Perception